Model-based evaluation of fouling mechanisms in powdered activated carbon/membrane bioreactor system - Xiong, Juan; Zuo, Xingtao; Zhang, Shi; Liao, Wei; Chen, Zhongbing (Water science and technology, 2019)
Identifying the fouling degree of a membrane bioreactor (MBR) provides guidance on the determination of suitable membrane cleaning methods. There is still a lack of knowledge on the effects of powdered activated carbon (PAC) refresh ratio on the MBR fouling mechanism. Major fouling mechanisms of an MBR with constant flow rate at different PAC replenishment ratios were investigated by individual and combined mechanistic fouling models. The root mean square errors were employed to assess the prediction accuracy of the used fouling models. The combined models showed better prediction. The cake-complete model provided far better fits of the transmembrane pressure data, and provided good fits of other individual model predictions regardless of the PAC refreshment ratio. Fourier transform infrared spectroscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy confirmed that the cake layer clogging was the main fouling mechanism followed by complete blockage and standard plugging. The cake-complete model may be used to predict the fouling mechanisms in PAC/MBR systems.
Keywords: Membranes, Artificial; prášky, zásypy, pudry; Charcoal; dřevěné a živočišné uhlí; odpad tekutý - odstraňování; Bioreactors; membrány umělé; odpadní vody; Powders; Waste Disposal, Fluid; bioreaktory; Sewage